2005
DOI: 10.1001/jama.294.4.455
|View full text |Cite|
|
Sign up to set email alerts
|

Acute Illnesses Associated With Pesticide Exposure at Schools

Abstract: Pesticide exposure at schools produces acute illnesses among school employees and students. To prevent pesticide-related illnesses at schools, implementation of integrated pest management programs in schools, practices to reduce pesticide drift, and adoption of pesticide spray buffer zones around schools are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 17 publications
1
44
1
Order By: Relevance
“…It is known that households with children commonly use and store pesticide products. [1][2][3] The use of pesticides at child care facilities, 4 on athletic fields, 5 and on school grounds 6 could all present potential exposures and health hazards to children. Because children's immune systems are still developing, they may provide less protection than adult immune systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that households with children commonly use and store pesticide products. [1][2][3] The use of pesticides at child care facilities, 4 on athletic fields, 5 and on school grounds 6 could all present potential exposures and health hazards to children. Because children's immune systems are still developing, they may provide less protection than adult immune systems.…”
mentioning
confidence: 99%
“…7,8 Children exposed to pesticides at home or at school have experienced acute toxic effects on their respiratory, gastrointestinal, nervous, and endocrine systems, as well as other serious medical outcomes. 6,9,10 Concern about the health effects of low-level exposure to pesticides in children has been increasing in recent years, generating a substantial number of epidemiologic studies demonstrating associations between pesticide exposures and childhood cancers. [11][12][13][14][15][16] However, most of these studies focused on parental occupational exposure or agricultural exposure, not exposure in the home.…”
mentioning
confidence: 99%
“…A 2005 study analyzed national surveillance data and found that 2593 cases of acute pesticide-related illnesses were associated with pesticide exposure in schools between 1998 and 2002 (Alarcon et al, 2005). Although there are no comparable data for child care centers, these exposures would be particularly concerning in child care settings, where children are younger than they are in the K-12 school system, and where large numbers of children spend full days.…”
mentioning
confidence: 99%
“…Pesticides that schools use in treating and maintaining school grounds have also been found to pose health risks to children (Alarcon et al, 2005;Gilden et al, 2012). or after treatment (Chatham-Stephens et al, 2011, and can also be tracked inside the building by students and faculty (Nishioka et al, 2001).…”
Section: Environmental Hazards In Schoolsmentioning
confidence: 99%
“…Pesticide exposure has been linked to acute flu-like symptoms as well as long-term more serious health issues like cancer. Alarcon et al (2005) identified 2593 school-related pesticide poisonings (from 1998-2002). Between 1993 and 1996, the Government Accountability Office identified around 2,300 reported school pesticide poisonings.…”
Section: Environmental Hazards In Schoolsmentioning
confidence: 99%